Linking Organizational Climate to Work Engagement in Higher Education Institutions - Dwi Amelia, Ifa; Saragih, Susanti (Journal Integration of Management Studies, 2026)
Organizational climate plays a crucial role in shaping employee work engagement, particularly in non-profit institutions, such as universities, where limited resources necessitate strategic human resource management. This study investigated how various dimensions of organizational climate, such as leadership, employee relations, organizational commitment, job satisfaction, and employee motivation, affected work engagement among 272 employees at a university in Bandung, Indonesia. Using simple and multiple regression analyses, the results show that, while all five dimensions significantly influence work engagement when tested individually, only organizational commitment and employee motivation remain strong predictors when examined together. These findings indicate that internal factors, such as employees’ emotional attachment to their organization and intrinsic motivation, play a more decisive role in fostering engagement than structural or relational factors. The results also extend the Social Exchange Theory by highlighting that reciprocal relationships between organizational support and employee dedication are primarily strengthened through mechanisms of commitment and motivation. From a practical perspective, this study highlights the importance of human resource strategies that foster internal motivation and enhance organizational commitment. These include implementing transparent reward systems, providing career development opportunities, and recognizing employee contributions. Such initiatives can help universities create a more supportive and engaging work environment, despite resource limitations. Overall, this study adds to the literature on organizational climate by identifying the most influential factors for building and sustaining work engagement within education institutions, offering both theoretical insights and actionable implications for HR practitioners.